PERAN PEER EDUCATOR DI DALAM PROGRAM AKTA KELAHIRAN ANAK JALANAN - Nahampun, Hery Syamsius; Sekar, Dwi Amalia Chandra (UI Scholars Hub, 2020)
The difficulty of reaching street children in a birth certificate program is due to a poor communication process in the context of adults to street children who prefer to interact with their peers. Although there are many studies in relation with this topic that illustrate several perspectives, there is still lack of research which describe the role of peer educator on a street children birth certificate program. This study uses a qualitative research method by interviewing 13 informants and group discussion with 7 informants which selected using purposive sampling techniques. The data findings are processed by categorizing the data in accordance with the study question and conceptual framework. It was found that peer educators play their role in spreading out information about birth certificates, play role as a counselor, motivator and including influencing the decision of street children to adopt the innovation of birth certificate. Peer educator proximity with peers is a major supporting factor to perform their role well. Also, time management was considered as a constraining factor in peer educators to perform their role.